Toxicity assessment on combined biological treatment of pharmaceutical industry effluents - (:unkn) unknown (I W A PUBLISHING, 2002)
This paper describes the wastewater characterization and aerobic/anaerobic treatability (oxygen uptake rate and biogas production measurement) of chemical-synthesis based pharmaceutical industry effluents in a nearby baker's yeast industry treatment plant. Preliminary experiments by the industry had indicated strong anaerobic toxicity. On the other hand, aerobic treatability was also uncertain due to complexity and unknown composition of the wastewater. The work in this study has indicated that the effluents of the pharmaceutical industry can be treated without toxicity in the aerobic stage of the treatment plant. Methanogenic activity tests with anaerobic sludge from the anaerobic treatment stage of the wastewater treatment plant and acetate as substrate have confirmed the strong toxicity, while showing that 30 min aeration or coagulation with an alum dose of 300 mg/l is sufficient for reducing the toxicity almost completely. Powdered activated carbon, lime and ferric chloride (100-1,000 mg/l) had no effect on reduction of the toxicity. Consequently, the pharmaceutical industry was recommended to treat its effluents in the anaerobic stage of the nearby baker's yeast industry wastewater treatment plan at which there will be no VOC emission and toxicity problem, provided that pretreatment is done.
Keywords: aerobic; anaerobic; fermentation; pharmaceutical industry; toxicity; treatment; wastewater